Demand Response and the Reform of Indirect Taxes in Pakistan - AHMAD, Ehtishaw (Institutional Knowledge at Singapore Management University, 1984)
The question of the appropriate tax rate for different commodities is important for policy making in a country like Pakistan. This involves not only revenue, which is an obvious and a major preoccupation of most governments, but also concerns the effects of tax changes on households in various circumstances, together with production decisions in many sectors of the economy. In this paper we shall be concerned with a preliminary evaluation of the Pakistan indirect tax system. We shall examine in further work, the analysis of direct taxes, the balance between direct and indirect taxes as well as the effects of indirect tax changes on production decisions. Thus we shall primarily focus on government revenue and effects on tax changes on households in different circumstances. This paper is also preliminary in that we shall consider only marginal changes from the status quo and we shall examine more substantial changes in subsequent work. The analysis follow g the methods used in our earlier work on tax reform in developing countries 'lee for example, Ahmad and Stern (1981), (1983a), (1983b), (1984), Ahmad, Coady and Stern (1984) and Stern (1984)1